Self-Efficacy Theory and Self-Healthcare Behavior of the Elderly - SIRITED, PHASIT; Thammaseeha, Noppawit (Journal of The Royal Thai Army Nurses, 2019)
At present, Thailand has an elderly population (aged 60 and above) of up to 11 million people, accounting for 17 percent of the total population. The key is that the late-aged population (aged 80 and over) will increase dramatically from 1.5 million people in 2017 to 3.5 Millions of people in the next 20 years. Although the problem of self-care and self help is not an issue now, up to 5%, of this late elderly population requires assistance in daily activities as they are Unable to engage in basic routines (e.g. eating themselves, in the bathroom, dressing themselves). especially the late seniors who cannot help themselves, There are as many as 19 percent of the elderly in the same age. Many research results indicate that the important factors that influence the expression of health behaviors of the elderly include self-efficacy; I.e. if the elderly have a high level of self-efficacy, they will have good and proper health behaviors. Therefore, the theory of self-efficacy is important in applying to ensure the elderly in performing healthy behaviors. Review of theoretical concepts on building one’s own abilities and study empirical evidence will allow health personnel to design appropriate activities to help older people be confident in expressing appropriate health behaviors.